Health self-perception is associated with life-styles and comorbidities and its effect on mortality is confounded by age. A population based study - Rañó-Santamaría, Oscar; Fernandez-Merino, Carmen; Castaño-Carou, Ana Isabel; Lado-Baleato, Óscar; Fernández-Domínguez, María José; Sanchez-Castro, Juan Jose; Gude, Francisco (Frontiers in Medicine, 2022)
Background: Health self-perception (HSP) is the individual and subjective concept that a person has of their state of health. Despite its simplicity, HSP is considered a valid and relevant indicator employed in epidemiological research and in professional practice as an overall measure of health. Objectives: 1) To describe and analyze the associations between HSP and demographic variables, lifestyle and diseases prevalent in a population and 2) to investigate the relationship between HSP and mortality. Material and Methods: In a primary care setting, we conducted a longitudinal study of a random populational sample of a Galician municipality, stratified by decade of life. A total of 1516 adults older than 18 years, recruited by the 2013–2015 AEGIS study, were followed-up for more five than years. During the clinical interview, data were collected on lifestyle and prevalent diseases. The HSP was grouped into 2 categories (good/poor). The statistical analysis consisted of a logistic regression, Kaplan-Meier curves and Cox regression. Results: A total of 540 (35.6%) participants reported poor HSP. At the end of the follow-up, 78 participants had died (5.1%). The participants with increased age and body mass index and chronic diseases (anxiety, depression, ischemic heart disease, diabetes and cancer) presented a poorer subjective health. A high level of physical activity and moderate alcohol consumption were associated with better HSP. A poorer HSP was associated with increased mortality, an association that disappeared after adjusting for the rest of the covariates (HR, 0.82; 95% CI 0.50–1.33). Conclusions: 1) HSP is associated with age, lifestyle and certain prevalent diseases. 2) A poorer HSP is associated with increased mortality, but this predictive capacity disappeared after adjusting for potential confounders such as age, lifestyle and prevalent diseases.